PROBLEMS WHICH MAR THETEACHING OF ORAL ENGLISH IN SECONDARY SCHOOLS IN NORTH-EASTERN NIGERIA - Garba, YUBA Asugu (International Journal of Psychosocial Rehabilitation, 2020)
The challenges that Nigeria face in recruiting and retaining qualified teachers cannot be overemphasized. The purpose of this study was to investing some of the challenges associated with teachers and teaching in English as well as identifying strategies that can be implemented to improve the working conditions of teachers as well as teaching in school in Nigeria. The study surveyed the problems of teaching Oral English in some selected secondary schools within Biu Local Government Area of Borno State. The sample size is 50 comprising of 8 secondary schools. A survey research design was adapted for the investigation. The research instruments. Include teaching staff questioners using the analysis of variance (ANOVA). The result of the finding reveals that there are problems in teaching Oral English in Biu secondary schools. Mother tongue interference, lack of experience and use of outdated textbook were major hacks to the teaching of Oral English. The schools or even the teachers should acquire up-to-date textbooks also, teacher be sent on in-service training and student are encouraged to communicate in English within and outside the classroom, so as to reduce the problems of mass failure in English Language Examination and other relevant examinations.Keyword- ,,